Managing patient safety and staff safety in nursing homes: exploring how leaders of nursing homes negotiate their dual responsibilities—a case study - Magerøy, Malin Rosell; Macrae, Carl; Braut, Geir Sverre; Wiig, Siri (Frontiers in Health Services, 2024)
Objective: Within healthcare, the role of leader is becoming more complex, and healthcare leaders carry an increasing responsibility for the performance of employees, the experience and safety of patients and the quality of care provision. This study aimed to explore how leaders of nursing homes manage the dual responsibility of both Health, Safety and Environment (HSE) and Quality and Patient Safety (QPS), focusing particularly on the approaches leaders take and the dilemmas they face. In addition, we wanted to examine how leaders experience and manage the challenges of HSE and QPS in a holistic way. Design/Setting: The study was designed as a case study. Data were collected through semi structured individual interviews with leaders of nursing homes in five Norwegian municipalities. Participants: 13 leaders of nursing homes in urban and rural municipalities participated in this study.Results: Data analysis resulted in four themes explaining how leaders of nursing homes manage the dual responsibility of HSE and QPS, and the approaches they take and the dilemmas they face: This is a provisional file, not the final typeset article 1. Establishing good systems and building a culture for a work environment that promotes health and patient safety. 2. Establish channels for internal and external collaboration and communication. 3. Establish room for maneuver to exercise leadership. 4. Recognizing and having the mandate to handle possible tensions in the dual responsibility of HSE and QPS. Conclusions: The study showed that leaders of nursing homes who are responsible for ensuring quality and safety for both patients and staff, experience tensions in handling this dual responsibility. They acknowledged the importance of having time to be present as a leader, to have robust systems to maintain HSE and QPS, and that conflicting aspects of legislation are an everyday challenge.